Surface Characterization of Biopolymer Micropatterns Processed by Ion-Beam Modification and PECVD - Manso Silván, M.; Valsesia, A.; Hasiwa, M.; Gilliland, D.; Ceccone, G.; Rossi, F. (Chemical vapor deposition, 2007)
The surface properties of poly(ethylene glycol) (PEG) and allylamine (ALL) have been used to create biomedical micropatterns by exploiting the antifouling character of ion beam‐treated PEG and the biofunctional properties of ALL films deposited using plasma‐enhanced (PE) CVD. For integration, the PEG film can be etched through a mask to subsequently deposit ALL in the formed cavities. Imaging mode X‐ray photoelectron spectroscopy (XPS) corroborates the contrasting chemistry, while time of flight secondary ion mass spectroscopy (ToF‐SIMS) demonstrates a net heparin adsorption inhibition onto PEG. The performance of the micropatterned platforms is supported by the selective response of L929 mouse fibroblasts. Poly(ethylene glycol) (PEG) and allylamine (ALL) have been used to create biomedical micropatterns by exploiting the antifouling character of PEG and the biofunctional properties of ALL films. The PEG film is etched through a mask to subsequently deposit ALL by PECVD in the formed cavities. Imaging‐mode X‐ray photoelectron spectroscopy, time‐of‐flight secondary ion mass spectroscopy, and the response of cultured fibroblasts corroborate the contrasting PEG vs. ALL chemistry.